2022
DOI: 10.1021/acs.jafc.2c04174
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Chitin Nanocrystals Greatly Strengthen the Stability of Resveratrol-Loaded Gliadin Nanoparticles

Abstract: Resveratrol (RES) is a natural polyphenol with a variety of health beneficial properties, but its application is greatly limited due to low aqueous solubility and poor bioavailability. This study aims to address these issues via gliadin nanoparticles stabilized with oxidized chitin nanocrystals (O-ChNCs) as a delivery system for RES. RES-loaded gliadin nanoparticles (GRNPs) were fabricated by an antisolvent method, and their formation mechanism was elucidated using zeta-potential, FTIR, XRD, and TEM. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For instance, the hydrophobic bond peaks of WPI and EDP at 2970 and 2923 cm –1 were shifted to 2927 and 2917 cm –1 , which indicated that hydrophobic interactions were presented between Myr and proteins. In addition, Myr showed a broad peak at 3415 cm –1 , corresponding to the O–H stretching vibration . With respect to the TMP–Myr and YP–Myr hydrogels, the characteristic peaks of hydrogen bonding were shifted from 3385 and 3389 cm –1 to 3404 and 3374 cm –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, the hydrophobic bond peaks of WPI and EDP at 2970 and 2923 cm –1 were shifted to 2927 and 2917 cm –1 , which indicated that hydrophobic interactions were presented between Myr and proteins. In addition, Myr showed a broad peak at 3415 cm –1 , corresponding to the O–H stretching vibration . With respect to the TMP–Myr and YP–Myr hydrogels, the characteristic peaks of hydrogen bonding were shifted from 3385 and 3389 cm –1 to 3404 and 3374 cm –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Myr showed a broad peak at 3415 cm −1 , corresponding to the O−H stretching vibration. 22 With respect to the TMP−Myr and YP−Myr hydrogels, the characteristic peaks of hydrogen bonding were shifted from 3385 and 3389 cm −1 to 3404 and 3374 cm −1 , respectively. Similar shift phenomena were also observed in the formation of the SPI− Myr, WPI−Myr, and EDP−Myr hydrogels.…”
Section: ■ Materials and Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…GR/OC composite nanoparticles were prepared following a previous study. 17 The resulting composite nanoparticles exhibited the highest encapsulation rate of RES with a ratio of 2 × 10 −3 of RES to gliadin. Additionally, for the OCh-GRNP suspension, the three-phase contact angle approached 90°at a gliadin/O-ChNC mass ratio of 1:1.5, indicating that the nanoparticles were most stable in solution at this ratio.…”
Section: Preparation Of Pickeringmentioning
confidence: 96%